Experimental investigation of Ti-6Al-4V with a biaxial tensile test setup at elevated temperature - Merklein, Marion; Suttner, Sebastian; Schaub, Adam (Key Engineering Materials, 2014)
The requirement for products to reduce weight while maintaining strength is a major challenge to the development of new advanced materials. Especially in the field of human medicine or aviation and aeronautics new materials are needed to satisfy increasing demands. Therefore the titanium alloy Ti-6Al-4V with its high specific strength and an outstanding corrosion resistance is used for high and reliable performance in sheet metal forming processes as well as in medical applications. Due to a meaningful and accurate numerical process design and to improve the prediction accuracy of the numerical model, advanced material characterization methods are required. To expand the formability and to skillfully use the advantage of Ti-6Al-4V, forming processes are performed at elevated temperatures. Thus the investigation of plastic yielding at different stress states and at an elevated temperature of 400°C is presented in this paper. For this reason biaxial tensile tests with a cruciform shaped specimen are realized at 400°C in addition to uniaxial tensile tests. Moreover the beginning of plastic yielding is analyzed in the first quadrant of the stress space with regard to complex material modeling.
LFT Import::2019-07-29 (2018)
Keywords: Formability; High performance metals; Sheet metal forming